PEMANFAATAN FASILITAS KESEHATAN PADA INFEKSI SALURAN PERNAPASAN AKUT (ISPA) ANAK BALITA DI WILAYAH KERJA PUSKESMAS REJOSARI - eva mayasari (Al Tamimi Kesmas: Jurnal Ilmu Kesehatan Masyarakat (Journal of Public Health Sciences), 2018)
Acute respiratory infection (ARI) is a respiratory tract infectious disease that attacks the upper respiratory and lower respiratory tract caused by infection of microorganisms or bacteria, viruses or rickets without or with lung parenchymal inflammation. This study aims to obtain in-depth information about the utilization of health facilities in acute respiratory infections (ARI) in children under five. The type of research used is qualitative with the design of Rapid Assessment Procedure (RAP). Informants in this study were mothers who had a toddler who had suffered from ARI is as many as 10 people and supporting informants are husband and health officer as many as 3 people. The results of this study found that most informants prefer to bring children affected by ARI to seek treatment for health services (doctor practice, health center and midwife practice), informants have a lack of knowledge about ISPA which includes the definition, causes and prevention of ARI, the dangers of ARD and family support for the behavior of the search for treatment is very good indicated from the frequent husband advise the wife to bring the child to treatment to health service and often the health officer give information about ISPA.